The nation in corte : electoral rights in vintismo - Domingues, José, 1960- (2023)
From subjects citizens : the conquest of citizenship in Portugal, from the 1820 Liberal Revolution to the present day / coordenação de Vital Moreira, José Domingues. - Lisboa : Universidade Lusíada Editora, 2023. ISBN 978-989-640-267-9.